2003
DOI: 10.1103/physreva.67.012311
|View full text |Cite
|
Sign up to set email alerts
|

Security of quantum key distribution with entangled qutrits

Abstract: We consider a generalisation of Ekert's entanglement-based quantum cryptographic protocol where qubits are replaced by quN its (i.e., N -dimensional systems). In order to study its robustness against optimal incoherent attacks, we derive the information gained by a potential eavesdropper during a cloning-based individual attack. In doing so, we generalize Cerf's formalism for cloning machines and establish the form of the most general cloning machine that respects all the symmetries of the problem. We obtain a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
121
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 37 publications
1
121
0
1
Order By: Relevance
“…The cases with two and four bases are studied analytically in [7], while in [10,11] the case with three mutually unbiased bases is studied numerically. The results obtained both with the most general unitary eavesdropping strategy and with the optimal quantum cloning machine are exactly the same.…”
Section: B Three Mutually Unbiased Basesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cases with two and four bases are studied analytically in [7], while in [10,11] the case with three mutually unbiased bases is studied numerically. The results obtained both with the most general unitary eavesdropping strategy and with the optimal quantum cloning machine are exactly the same.…”
Section: B Three Mutually Unbiased Basesmentioning
confidence: 99%
“…In these sections we find the optimal eavesdropping strategy and we compare the results with those ones obtained by an optimal quantum cloning machine. The generalization to four-dimensional systems and the comparison with the corresponding results derived from cloning attacks [7,10,11] is discussed in Sec. III, in a protocol with only two unbiased bases.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum communication complexity protocol with two entangled qutrits has been proposed [8], and it has been proven that, for a broad class of protocols the entangled state of two qutrits can enhance the efficiency of solving the problem in the quantum protocol over any classical one if and only if the state violates Bell's inequality for two qutrits. By making use of the entangled qutrits, a generalization of Ekert's entanglement-based quantum cryptographic protocol has been discussed [9]. By means of the orbital angular momentum of the photons, the experimental implementation of producing, transmitting, and reconstructing the qutrit has been reported [10].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of non-local correlations are in fact greater in case of entangled qutrits (three-level systems) than entangled qubits [8]. Several cryptographic protocols have been devised using qutrits which are argued to be highly secure against symmetric attacks [9][10][11]. Recently it has also been demonstrated that qutrits can be useful for certain purposes of quantum simulation [12], quantum computations [13][14][15] and quantum communication [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%